Direct conversion of human fibroblasts into hepatocyte-like cells by ATF5, PROX1, FOXA2, FOXA3, and HNF4A transduction. Issue 1 (December 2017) - Nakamori, Daiki; Akamine, Hiroki; Takayama, Kazuo; Sakurai, Fuminori; Mizuguchi, Hiroyuki
Abstract Recently, it has been reported that human hepatocyte-like cells can be generated from fibroblasts by direct reprogramming technology. However, the conversion efficiency of human induced hepatocyte-like cells (hiHeps) is not high enough. In addition, comparative analysis with the existing models of hepatocytes, such as human iPS cell-derived hepatocyte-like cells and primary human hepatocytes, has not been sufficiently carried out. In this study, we screened hepatic transcription factors for efficient direct hepatic reprogramming and compared hepatic functions between hiHeps and other existing hepatocyte models. We found that human fibroblasts were efficiently converted into hiHeps by using a combination of ATF5, PROX1, FOXA2, FOXA3, and HNF4A (albumin+/alpha-1 antitrypsin+ cells = 27%, asialoglycoprotein receptor 1+ cells = 22%). TheCYP expression levels and CYP activities in hiHeps were higher than those in human iPS cell-derived hepatocyte-like cells, but lower than those in short-term (4 hr) cultured primary human hepatocytes and primary human hepatocytes collected immediately after thawing. These results suggested that functional hiHeps could be efficiently generated by ATF5, PROX1, FOXA2, FOXA3, and HNF4A transduction. We believe that hiHeps generated by our method will be useful for the drug-discovery activities such as hepatotoxicity screening and drug metabolism tests.